Gambaran Tingkat Pengetahuan Bantuan Hidup Dasar Tim Bantuan Medis Baswara Prada Universitas Warmadewa - Kadek Dean Ariska Aryawangsa; Luh Gede Sri Yenny; I Ketut Tangking Widarsa (Aesculapius Medical Journal, 2023)
Knowledge of Basic Life Support (BLS) is considered basic knowledge for the medical team because it is needed to provide first aid to victims who experience cardiac arrest. The Baswara Prada Medical Assistance Team (TBM) is an organization engaged in medical emergencies under the auspices of the BEM-LM FKIK Warmadewa University. This study aims to analyze and describe the level of basic life support knowledge of the Baswara Prada Medical Assistance Team (TBM) at the Faculty of Medicine, Warmadewa University. This research is a descriptive study using a cross sectional approach. This research was conducted on 101 respondents of members of the Baswara Prada Medical Assistance Team, Warmadewa University. Data was collected by giving a questionnaire in the form of a google form containing questions about Basic Life Support (BLS) to members of the Baswara Prada Medical Assistance Team. The results of the research data were analyzed descriptively and presented in the form of tables or graphs. The results showed that the knowledge level of Basic Life Support (BLS) of the Baswara Prada Medical Assistance Team (TBM) of the Faculty of Medicine and Health Sciences, Warmadewa University was at a good level with a percentage of 95.1% and at an adequate level with a percentage of 4.9%.